The Value and Validity of Self-Reported Survey Data on the Rape Experiences of College Students - Krebs, Christopher (Violence against women, 2022)
Self-reported survey data on the extent and nature of rape and sexual assault experienced by a population represent an important source of information because these crimes often go unreported, and are thus undercounted in law enforcement or other official statistics. This article compares Campus Climate Survey Validation Study (CCSVS) data to Clery Act data in an effort to (1) assess the validity of the CCSVS data and the Clery Act data based on the extent to which they corroborate one another, and (2) estimate the extent to which Clery Act data potentially underestimate the true incidence of rape. The results help to establish the extent to which self-report surveys on sexual victimization are needed to understand the magnitude of the problem among a given population.